SIMILAR BUT NOT ALIKE: THE FRAMING OF COVID-19 IN INDONESIAN AND MALAYSIAN NEWSPAPERS - Haekal Adha Al Giffari; Shafizan Mohamed (Metacommunication: Journal of Communication Studies, 2021)
The COVID-19 pandemic has certainly caused havoc all over the world. Governments, healthcare personnel, and the general public are all struggling to survive the health crisis. In such calamity, the media plays an important role as it is able to impact public attitude and response towards the pandemic. Malaysia and Indonesia are two neighbouring countries that are equally affected by the pandemic. These countries share the same language and geographic location, but they have distinct populations, government systems, and ethnic identities. This study compares the news framing of Covid-19 in Malaysian and Indonesian newspapers to understand how socio-political and cultural similarities and differences affect how the health crisis is framed and presented. The Star (Malaysia) and Detik (Indonesia) were chosen to be studied in this paper, with a total of 369 news pieces obtained between 60 days after the first local COVID-19 case was discovered in the respective country. The findings suggest that the framing of Malaysian online newspapers was action-oriented, whereas the framing of Indonesian online newspapers was uncertainty-oriented. In addition, Malaysian and Indonesian internet newspapers were quick to report on the Covid-19 news. Both cited the government as their primary source and addressed risk bearers as their primary focus. This shows that despite their geographical proximities, the two countries had distinct ways of covering the pandemic.